Cooperative Learning Pedagogy in Teaching an Inclusive Class Rooms - Husin, Mohd Razimi; Jauhari, Ahmad Faqeh Abidin; Wan Mohd Allwee, Wan Humairaa'; Zurkarnain, Muhammad Arash Ilham (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2024)
Pedagogi melibatkan aspek pengajaran, pembelajaran, dan interaksi di dalam konteks pendidikan. Pedagogi mempelajari bagaimana individu belajar, cara penyampaian yang efektif, serta pembinaan persekitaran pembelajaran yang menyokong perkembangan individu secara menyeluruh. Matlamat utama pedagogi adalah mencipta persekitaran pembelajaran yang membolehkan pemahaman, kemahiran, dan nilai-nilai yang relevan bagi perkembangan holistik pelajar. Dengan memahami prinsip-prinsip pedagogi dan mengaplikasikannya secara berkesan, guru dapat menjadi fasilitator pembelajaran yang berkesan dan membantu pelajar mencapai potensi mereka secara maksima. Murid berkeperluan pendidikan khas (MBPK) merujuk kepada kanak-kanak yang mempunyai atau memerlukan keperluan pendidikan yang berbeza dari kebanyakan kanak-kanak yang lain. Keberkesanan strategi pengajaran guru dalam pendidikan inklusif dapat dilihat apabila murid-murid memberikan respon yang amat baik terhadap pembelajaran yang diberikan untuk membantu murid-murid diskalkulia menguasai subjek yang diajarkan. Cooperative Learning Pedagogy in Teaching an Inclusive Class Rooms Abstract: Pedagogy involves aspects of teaching, learning and interaction within an educational context. Pedagogy studies how individuals learn, effective delivery methods, and the development of learning environments that support the holistic development of individuals. The main goal of pedagogy is to create a learning environment that enables understanding, skills, and values relevant to the holistic development of the learner. By understanding the principles of pedagogy and applying them effectively, teachers can become effective facilitators of learning and help learners reach their full potential. Students with special educational needs (MBPK) refer to children who have or require different educational needs from most other children. The effectiveness of teachers' teaching strategies in inclusive education can be seen when students respond very well to the learning provided to help students with dyscalculia master the subject taught. Keywords: Inclusive Class, Pedagogy, Teaching Strategies.